Socio-economic space and the new face of globalisation - Korenik, Stanisław (Przestrzeń społeczno-ekonomiczna wobec nowego oblicza globalizacji, 2024)
Aim: The aim is to identify and indicate the directions of transformation in the globalization process and the changing role of socio-economic space in this new phase of globalization, associated, among others, with the increasing regional character of global processes. Methodology: The article employs a broad critical analysis of the subject literature, assessment of secondary data, and expert opinions. Findings: The article indicates that in recent years, the globalization process has undergone significant transformations, resulting in an increased importance of socio-economic space in location decision-making. Implications and recommendations: The findings suggest that current development processes must increasingly take into account local and regional networks and supply chains. The remoteness of suppliers from domestic markets leads to increased uncertainty and higher business operation costs. Originality/value: The value of the article lies in linking the rising uncertainty in global markets with the need to redefine spatial security, which entails the construction of new socio-economic relationships.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 31-38
Keywords: Dolny Śląsk